Asianfail : narratives of disenchantment and the model minority - Ty, Eleanor Rose, 1958- (Asian American experience., 2017)
Eleanor Ty's bold exploration of literature, plays, and film reveals how young Asian Americans and Asian Canadians have struggled with the ethos of self-sacrifice preached by their parents. This new generation's narratives focus on protagonists disenchanted with their daily lives. Many are depressed. Some are haunted by childhood memories of war, trauma, and refugee camps. Rejecting an obsession with professional status and money, they seek fulfillment by prioritising relationships, personal growth, and cultural success. As Ty shows, these storytellers have done more than reject a narrowly defined road to happiness. They have rejected neoliberal capitalism itself. In so doing, they demand that the rest of us reconsider our outmoded ideas about the so-called model minority.